Gestational Trophoblastic Disease: Opportunities for a National Registry Collaboration. Issue 6 (July 2016) - Rozenholc, Alexandre; Dodge, Jason; Bréguet, Magali; Sauthier, Philippe
Abstract : Objective: In rare entities such as gestational trophoblastic disease (GTD), only multi-institutional registries can gather significant number of patients to build up valuable clinical databases. No Canada-wide GTD registry currently exists. We conducted a survey among members of the Canadian Society of Gynecologic Oncology (GOC) to investigate their interest in a pan-Canadian GTD registry. We also took the opportunity to explore their management of GTD. Methods: An electronic survey was conducted. The target group was the entire GOC Canadian Membership. The survey consisted of 25 questions. Results: The survey participation rate was 39% (67/171). Seventy-six percent of responders treat patients with molar pregnancy or gestational trophoblastic neoplasia (GTN), and the majority treat only 5 or less cases of molar pregnancy and 5 or less cases of GTN per year. In cases of low-risk GTN, 80% of responders use generally recommended single-agent chemotherapy regimens. In cases of high-risk GTN, 76% use generally recommended multiagent chemotherapy regimens. Most respondents do not submit either molar pregnancy or GTN patients to any formal registry, although the vast majority (92%) would do so if they had access to a registry, given that most believe that a registry can or probably can help patients with GTD. Responders indicated that the jurisdiction of such a registry should be national (59%), provincial (25%), and regional (11%). Conclusions: Despite some variation, responders were generally knowledgeable about contemporary management issues. Canadian Society of Gynecologic Oncology members acknowledge generally low exposure to GTD patients in Canada and support the creation of a national GTD registry to facilitate optimal patient care, education, and research.